English Learning Interest of the Junior High School Students: A Mixed Methods Study - Sugianto; Sofendi; Ismail Petrus (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The pandemic has provided a significant change in the learning system. It changed the teachers and students’ methods in learning. During pandemic, the learning process through screen and learning management system. That condition gave positive and negative effect in learning. The positive impact of the pandemic is that teachers and students are able to used online learning methods and improve their skills in using internet and IT, while the negative impact is that students decreased their interest in learning because students tend to confused and misunderstood on the teachers’ explanations. The purpose of this study was to analyze how the interest in learning English of nine grade students, why is the student on that level of interest, and whether there is a significant relationship between students' learning interest and English mastery. The research method used was a mixed-method study with 36 participants of Junior High School students. The convergent parallel design used in this study. The instruments used are questionnaires, interview, and students’ final score in the first semester in academic year 2022/2023. Based on the data obtained, there are 9 students who have a high level of interest in English, 26 students have a medium level of interest in English, and 1 student has a low level of interest in English. The result showed that there is a significant relationship between students' English learning interest and students’ English mastery and a positive effect on students' English skills.